Pengaruh investment opportunity set (IOS), mekanisme good corporate governance dan reputasi KAP terhadap kualitas laba perusahaan (Studi empiris pada perusahaan property and real estate yang terdaftar di Bursa Efek Indonesia 2010-2012) - Erikson Simamora; Amries Rusli Tanjung; Julita ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the effect of investment opportunity set (IOS), good corporate governance mechanism (audit committee, independent directors, institutional ownership, managerial ownership) and public accounting firm's reputation on quality of corporate earnings. The sample was taken using the method of purposive sampling from property and real estate company listed on the Indonesia Stock Exchange in 2010 until 2012. Obtained 81 samples from 33 property and real estate company for 3 years. Hypothesis testing is performed using multiple linear regression analysis. The results of this study indicate that audit committee have significant effect on corporate earnings. While investment opportunity set (IOS), independent directors, managerial ownership and institutional ownership of the firm's reputation does not have significant effect on quality of corporate earnings.Keyword: Investment opportunity set (IOS), good corporate governance mechanism, public accounting firm’s, quality of corporate earnigs.